Molecular detection of SARS-CoV-2 and medically important respiratory and gastrointestinal virus pathogens on Thai currency - Nattamon Niyomdecha; Chanakan Suttasit; Attasit Boonyont; Thanchira Saita; Waratchaya Rodraksa; Achiraya Phanitmas; Nattapong Yamasamit; Kantima Sangsiriwut; Pirom Noisumdaeng (Scientific Reports)
Abstract Fomite-mediated viral transmission through using cash might be a potential risk to human health. Persistence of SARS-CoV-2, and other medically important viruses was investigated. A total of 300 samples (i.e., 150 banknotes and 150 coins) were randomly collected from nineteen fresh markets distributed across seventeen districts of Bangkok, Thailand. Every banknote or coin was entirely swabbed and generated a total of 100 pool samples. Total viral nucleic acid was extracted and subjected for multiplex real-time qRT-PCR using Allplex™ SARS-CoV-2/FluA/FluB/RSV assay and Allplex™ GI-virus assay. The results revealed detection rate of 4% (4/100), and they were only detected in banknote pooled samples. Two samples collected from fish shops tested positive for SARS-CoV-2 (2%, 2/100); meanwhile, two samples (2%, 2/100) from pork and chicken shops tested positive for rotavirus A. None of pool samples were detected for influenza A and B viruses, respiratory syncytial virus, norovirus genogroup I and II, adenovirus, astrovirus, and sapovirus. Phylogenetic analysis demonstrated that rotavirus A belonged to genotype G8; meanwhile, SARS-CoV-2 resembled omicron GRA JN.1 sub variant. Our finding is the first report for demonstrating the presence of SARS-CoV-2 and rotavirus A in Thai banknotes on real-world situation, implying the potential risk to human health and safety.